The Analysis of Mahmud Al-Zamakhshari’s Works on Islamic Studies - Abzalova Farida (Indonesian Journal Publisher, 2025)
The mentioned article is devoted to the Islamic studies of Mahmud al-Zamakhshari and the analysis of his religious and scholarly works. The author of the article provides information about the works of al-Zamakhshari and classifies them according to their thematic fields. The article gives a detailed account of such prominent works as al-Kashshaf, Nukat al-iʿrab, Ruusul al-Masʾil, al-Faʾiq fī Gharib al-Ḥadith, Nawabigh al-Kalim, and Atwaquz zhab fī al-Mawaʿiẓ wa al-Khuṭab. Furthermore, the author provides detailed descriptions of these works and examines the manuscript copies preserved in various libraries of the world